The interplay between knowledge management and organizational performance measurement through the mediating effect of innovation capability - Azzam A. Abou-Moghli (Knowledge & Performance Management)
Knowledge management is a ‘know-how’ expression through which companies can access and apply their shared knowledge to achieve innovation, improve performance, and attain long-term competitive advantage. The present study investigates the association between knowledge management and organizational performance measurement with innovation capability mediating in the Jordanian Telecommunication sector. Descriptive and inferential statistics, such as regression analysis and structural equation modeling, were used to analyze 575 responses from employees working in major telecommunication companies like Zain, Orange, and Umniah. The performances of knowledge management impact on organizational performance measurement results were positive, with the R-square amounting to 0.803. The change of each predictor variable in terms of B was: Knowledge Creation, 0.179; Knowledge Storage, 0.196; Knowledge Sharing, 0.399; Knowledge Application, 0.221; and Knowledge Evaluation, 0.234. Further, Innovation capability positively mediates the impact of knowledge management on organizational performance measurement. Overall, the study’s findings emphasize that an enterprise should effectively handle its intellectual assets and enhance its innovation capabilities since it may have the potential to hold a competitive advantage and overall performance in an advanced era. Acknowledgment The author is grateful to Middle East University, Amman, Jordan, for the financial support to cover this article’s publishing fee.